Gender and Age Differences with Myocardial Infarction Symptom Presentation and In-Hospital Mortality - Gulnara Bedelbayeva (Journal of Global Pharma Technology, 2018)
Myocardial infarction (MI) is the main cause of death and disability worldwide; it increases the risk of many chronical diseases. This study assessed the correlation between the sex and age of patients with chest pain symptoms and the in-hospital mortality rate. Observational study of 6513 registry patients (2741 women and 3772 men) from Cardio logical Centre of Myocardial Infarction of Almaty (Kazakhstan), 2010-2011. Differences between study groups were assessed by χ2 test for categorical variables, the t test for continuous variables, and the nonparametric Wilcoxon rank sum test for median comparisons.  The proportion of MI patients who presented without chest pain was significantly higher for women than men. There was a significant interaction between age and sex with chest pain at presentation, with a larger sex difference in younger than older patients, which became attenuated with advancing age. Multivariable adjusted age-specific odds ratios (ORs) for lack of chest pain for women (referent, men) were younger than 45 years, 1,30; 45 to 54 years, 1,26; 55 to 64 years, 1,24; 65 to 74 years, 1,13; and 75 years or older, 1,03. Two-way interaction (sex and age) on MI presentation without chest pain was significant (P<0,001). The in-hospital mortality rate was 14,6% for women and 10,3% for men. Younger women presenting without chest pain had greater hospital mortality than younger men without chest pain, and these sex differences decreased or even reversed with advancing age, with adjusted OR for age younger than 45 years, 1,18; 45 to 54 years, 1,13; 55 to 64 years, 1,02; 65 to 74 years, 0,91 and 75 years or older, 0,81. The 3-way interaction (sex, age, and chest pain) on mortality was significant (P <0,001). In this registry of patients hospitalized with MI, women were more likely than men to present without chest pain and had higher mortality than men within the same age group, but sex differences in clinical presentation without chest pain and in mortality were attenuated with increasing age.Keywords: Myocardial Infarction, Chest Pain, Mortality, Sex, Age.